Exploring The Teacher Identity in the Context of EFL Teaching - Andjani, Inara Fatika; Khayan , Muhammad; Hidayatullah , Julyan; Fauzana (Verba: Journal of Applied Linguistics, 2024)
This qualitative study investigates the dynamic creation of teacher identity in the context of English language teaching (ELT). The study examines the complex interplay of professional identity and personal experience, based on the idea that teacher identity develops through experiences and interactions. The study sheds light on the various features of teacher identity creation using semi-structured interviews with a non-native English instructor in Semarang, Indonesia. According to the findings, professional identity is shaped by a commitment to language fluency, adaptability to varied teaching roles, and a balance of academic rigor and student well-being. Furthermore, personal experiences, such as socioeconomic background and educational trajectory, have a substantial impact on teacher identity development. The study emphasizes the necessity of matching teacher training programs with the difficulties of diverse classrooms and addressing research gaps for non-native English-speaking teachers. Finally, this study contributes to a better understanding of teacher identity creation and the consequences for effective pedagogical practices in ELT contexts, particularly in the private course setting that demands flexibility and a student-centered approach to meet the specific needs of learners.